2004
DOI: 10.1172/jci20641
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a critical contribution of haploinsufficiency in the complex pathogenesis of Marfan syndrome

Abstract: Marfan syndrome is a connective tissue disorder caused by mutations in the gene encoding fibrillin-1 (FBN1). A dominant-negative mechanism has been inferred based upon dominant inheritance, mulitimerization of monomers to form microfibrils, and the dramatic paucity of matrix-incorporated fibrillin-1 seen in heterozygous patient samples. Yeast artificial chromosome-based transgenesis was used to overexpress a disease-associated mutant form of human fibrillin-1 (C1663R) on a normal mouse background. Remarkably, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
122
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 194 publications
(130 citation statements)
references
References 47 publications
4
122
0
4
Order By: Relevance
“…Along the same lines, another study has indicated that a specific Cterminal peptide of fibrillin-1 (cb-EGFs 26-31) can modulate TGF-b bioavailability by competing LTBPmediated binding of the LLC to the N terminus of fibrillin-1 [64]. MFS-like vascular disease was also observed in mice heterozygous for a missense mutation (C1039G) that eliminates one of the obligatory cysteines of cb-EGF11 [8,65]. However, unlike mgR/mgR mice, C1039G/+ mice do not routinely progress to aortic dissection despite showing all of the hallmark histological features of MFS and progressive aortic root dilation.…”
Section: Roles Of Fibrillins In Organ Development and Functionmentioning
confidence: 96%
“…Along the same lines, another study has indicated that a specific Cterminal peptide of fibrillin-1 (cb-EGFs 26-31) can modulate TGF-b bioavailability by competing LTBPmediated binding of the LLC to the N terminus of fibrillin-1 [64]. MFS-like vascular disease was also observed in mice heterozygous for a missense mutation (C1039G) that eliminates one of the obligatory cysteines of cb-EGF11 [8,65]. However, unlike mgR/mgR mice, C1039G/+ mice do not routinely progress to aortic dissection despite showing all of the hallmark histological features of MFS and progressive aortic root dilation.…”
Section: Roles Of Fibrillins In Organ Development and Functionmentioning
confidence: 96%
“…Both heterozygous and homozygous mice with a fully expressed missense mutation in Fbn1 were compared to wild-type mice. Those with a missense mutation in Fbn1 had previously been shown to have many phenotypic features of MFS [26]. MV length and thickness were increased by postnatal day 6.5 in the heterozygous mice compared to wild-type mice, and they were also increased in the homozygous mice compared to the heterozygous Fbn1 mutant mice [27].…”
Section: Increased Tgfβ Signaling In Marfan Syndromementioning
confidence: 98%
“…Since the Wrst description of an FBN1 mutation (Dietz et al 1991), the role of haploinsuYciency in the pathogenesis of MFS has been the subject of intensive investigations and discussions. Mouse models suggested a critical threshold of functional microWbrils in the disease presentation of MFS (Pereira et al 1999) and provided evidence for a critical contribution of haploinsuYciency by showing that half-normal amounts of Wbrillin-1 can be insuYcient to initiate productive microWbrillar assembly (Dietz and Mecham 2000;Judge et al 2004). Furthermore, mouse MFS models showed that mice Fig.…”
Section: A a A T T C C C C T T A A A T T C T C Ca A C T C C A T T A Gmentioning
confidence: 99%
“…(Fukushima et al 1990;Dierlamm et al 2003;Shur et al 2003;Pramparo et al 2005), are not included here because these chromosomal abnormalities aVect not only FBN1 but also several other genes. For similar reason, entire FBN1 allele deletions reported by Hutchinson et al (2003) and Adès et al (2006) as well as mentioned by Judge et al (2004) are not included. In accordance with the guidelines of the HGVS (http://www.hgvs.org/mutnomen), in the description of deletions aVecting only the FBN1 gene (FBN1:) position +1 corresponds to the Wrst nucleotide of the FBN1 reference sequence (GenBank NC_000015.8) at genomic DNA (g) level, to the A of the ATG start codon of the mRNA reference sequence (GenBank NM_000138.3) at cDNA (c) level and to the translation initiator methionine of the reference sequence (GenBank NP_000129.2) at protein (p) level, respectively b Detection rate (#1/#2) is given as the number of cases with the respective mutation (#1) among patients screened in the corresponding study (#2) c MFS Marfan syndrome d Described in relation to the human genome reference sequence (NCBI build 36.1, March 2006), starting with the Wrst-deleted and ending with the last-deleted nucleotide.…”
Section: T T T T Gaa Ta T T Ttca G Tac T T Taa Aca Gc C Tac Ccc a T Amentioning
confidence: 99%